Strengthening the Role of Women in Empowering Mosque Functions After the Covid 19 Pandemic with a Social Entrepreneurship Approach - Zeni Luthfiyah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
This service aims to increase women's awareness and capacity in managing the function of an economy-based mosque through Zakat, Infak, Shodaqoh, and Waqf (Ziswaf) funds. This departs from the fact in the community around the assisted mosque that in every majlis of women-based religious activities there is an economic sector that is built and developed with a savings and loan cooperative system. especially during the COVID-19 pandemic, the community's need for social institutions like this is very high, this can be seen from the number of borrowers at one of the women's ta'lim majlis which has increased sharply. Therefore, it is important to help increase their role and capacity, in the process of social change and improving people's welfare. Thus, institutionally mosques and mosque congregations as a community of the nation-state can contribute optimally in the national development process. The ability to master mosque empowerment strategies by developing zakat, infaq, shadaqah, and waqaf (ZISWAF) instruments is important to be mastered by mosque welfare officials and women driving economic activity in majlis ta'lim. The method applied in this program is Participatory Rural Appraisal (PRA) which prioritizes critical dialogue using object/community-based disclosure, to obtain a real perspective in the minds of the target object and at the same time fulfil the paradigmatic alignment as mentioned above. The approach taken in this program is a social entrepreneurship approach, which combines increasing the value of resources economically and streamlining social goals and missions. This approach aims to improve social aspects, as well as implement strategies that are integrated between social and economic aspects.